2021
DOI: 10.3390/sym13060945
|View full text |Cite
|
Sign up to set email alerts
|

Linear Diophantine Fuzzy Relations and Their Algebraic Properties with Decision Making

Abstract: Binary relations are most important in various fields of pure and applied sciences. The concept of linear Diophantine fuzzy sets (LDFSs) proposed by Riaz and Hashmi is a novel mathematical approach to model vagueness and uncertainty in decision-making problems. In LDFS theory, the use of reference or control parameters corresponding to membership and non-membership grades makes it most accommodating towards modeling uncertainties in real-life problems. The main purpose of this paper is to establish a robust fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In this section, we present some basic results and examples related to linear Diophantine fuzzy sets [3,4] and to BCK/BCI-algebras [23].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present some basic results and examples related to linear Diophantine fuzzy sets [3,4] and to BCK/BCI-algebras [23].…”
Section: Preliminariesmentioning
confidence: 99%
“…To eliminate these restrictions by using reference parameters, Riaz and Hashmi [3] in 2019 found a new extension of fuzzy sets and called it linear Diophantine fuzzy sets (LDFS). Using the corresponding reference parameters to the membership and non-membership fuzzy relations, S. Ayub et al [4] established a robust fusion of LDFSs and binary relations and introduced linear Diophantine fuzzy relations.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, Atanassov [21] proposed the idea of intuitionistic fuzzy relation (IF relation) by promulgating the constraint that the sum of association and disassociation grades should not be greater than 1. Recently, Ayub et al [22], proposed a beautiful extension of the IF relation, named linear Diophantine fuzzy relation (LDF relation), with a robust application in decision-making, by the influence of the novel concepts of LDFSs. Hashmi et al [23] suggested the conceptualization of m-polar neutrosophic topology with applications to MADM.…”
Section: Introductionmentioning
confidence: 99%
“…In 1936, Birkhoff and von Neumann [20] considered the orthomodular lattice as quantum logic for studying the algebraic structure of quantum mechanics. There are many extensions of Pawlak's rough set, such as fuzzy rough sets [21,22], covering based rough sets [23][24][25], probabilistic rough sets [26,27], soft rough sets [28][29][30][31], Diophantine fuzzy rough sets [32][33][34][35], multi-granulation rough sets [36][37][38], hesitant fuzzy rough set [39] and so on. However, as far as I know, there is only a little literature addressing the rough sets and quantum logics together.…”
Section: Introductionmentioning
confidence: 99%